Selection of Multi-Drug Resistant Influenza A and B Viruses under Zanamivir Pressure and their Replication Fitness in Ferrets. Issue 4 (May 2018) - Oh, Ding Yuan; Panozzo, Jacqueline; Vitesnik, Sophie; Farrukee, Rubaiyea; Piedrafita, David; Mosse, Jennifer; Hurt, Aeron C
Background: Intravenous zanamivir has been used to treat patients with severe influenza. Because the majority of cases (including immunocompromised patients) require the drug for an extended period of treatment, there is a higher risk that the virus will develop resistance. Therefore, knowing the possible amino acid substitutions that may arise in recently circulating influenza strains under prolonged zanamivir exposure and their impact on antiviral susceptibility is important. Methods: Influenza A(H1N1)pdm09, A(H3N2) and B virus were serially passaged under increasing zanamivir pressure in vitro . Neuraminidase (NA) mutations that arose were introduced into recombinant viruses and the susceptibility to oseltamivir, zanamivir, peramivir and laninamivir was determined. The replication fitness of the recombinant variants was assessed in the ferret. Results: NA mutations E119D (N1 numbering) and E117D (B numbering) were detected in A(H1N1)pdm09 and B (Victoria-lineage) viruses respectively and were associated with reduced susceptibility to all four NA inhibitors. No NA mutations were detected in the A(H3N2) or B (Yamagata-lineage) viruses. In ferrets, the A(H1N1) pdm09 E119D variant caused a lower degree of morbidity and the mutation was found to be unstable with E119 reverted virus detected 4 days post-infection of ferrets with the variant E119D virus. In contrast, the influenza B E117D variant was genetically stable in ferrets, caused a noticeable level of morbidity but had a significant reduction in replication fitness compared to wild-type virus. Conclusions: The NA mutations E119D in influenza A(H1N1)pdm09 and E117D in influenza B viruses that arose under zanamivir pressure conferred resistance to multiple NA inhibitors but had compromised viral replication in ferrets compared to wild-type virus without antiviral drug pressure.